Clinical characteristics of patients with Aspergillus species isolation from respiratory samples: Comparison of chronic pulmonary aspergillosis and colonization - Ohara, Sayaka; Tazawa, Yoko; Tanai, Chiharu; Tanaka, Yoshiaki; Noda, Hiromichi; Horiuchi, Hajime; Usui, Kazuhiro (Respiratory investigation, 2016)
With advancements in anti-fungal drugs, it has become more important to correctly diagnose chronic pulmonary aspergillosis (CPA); however, it is not easy to distinguish CPA from colonization when Aspergillus species are isolated from respiratory samples. The aim of the study was to clarify the particular clinical characteristics of patients with CPA vs. those with colonization. We retrospectively reviewed the medical records of 110 patients with Aspergillus species isolation from respiratory samples, to analyze and compare the differences between CPA and colonization of the Aspergillus species. The median age of all analyzed was 71 years (range: 31–92 years); 64 were female (58%). The most frequently cultured Aspergillus species was Aspergillus fumigatus (48.3%), followed by A. niger (29.2%). Thirty patients (27.4%) were diagnosed with CPA, vs. 75 (68.2%) with colonization and 5 (4.5%) with allergic bronchopulmonary aspergillosis. Compared with the colonization group, the CPA group included more males (CPA vs. colonization: 49.3% vs. 13.3%) and subjects with a low body mass index (18.45kg/m2 vs. 21.09kg/m2). As for the underlying pulmonary diseases, the patients with CPA showed a significantly higher prevalence of sequelae of pulmonary tuberculosis (40% vs. 8%) and a history of thoracic surgery (43% vs. 13%) than those with colonization. Asthma was less frequent in the CPA group than in the colonization group (0% vs. 20%). We found no significantly important underlying extrapulmonary diseases. Patients with CPA display clinical characteristics distinct from those seen in subjects with colonization.